Assessing Price Behavior of Tuna in Indonesia - Ketut Sukiyono; Putri Suci Asriani; Redy Badrudin; Nola Windirah; Rahmi Yuristia; Musriyadi Nabiu (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight ResearchPrices are often a signal for producers to produce or market products, including the price of tuna.Four price behaviors, namely trends, seasonal variation, variability and instability, and market integration, are important to study in designing business development plans.Tuna prices in Indonesia tend to have a statistically positive trend.Tuna prices tend to be stable, or do not have high variability, throughout the observations and indicate a low price risk.The price of tuna fish in each port is formed independently and is not influenced and influences each other between the markets observed.AbstractPrices of agricultural and fisheries products have always been a concern not only by producers and consumers but also by the government in designing policies to control and stabilize these prices to protect the poor. Therefore, a study of price behavior is crucial to be scrutinized more deeply and comprehensively. This research is aimed at examining and analyzing tuna (Thunnus spp.) price behavior in terms of their seasonal, trend, variability, and instability behavior as well as their market integration. For this purpose, monthly data of tuna prices from 2011:1 to 2019:12 in five tuna production centers (provinces) in Indonesia, including North Sulawesi, West Papua, Aceh, North Maluku, and Bali, at the national level were applied. It was found that tuna prices have a positive trend and are statistically significant, excluding in West Papua. The study also found that price variability and instability were insignificant during observations. The study also concluded that the tuna price in every single province in Indonesia is formed independently.